2019
DOI: 10.3390/info10110352
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age, Gender, and Cognitive Ability on the Susceptibility to Persuasive Strategies

Abstract: The fact that individuals may react differently toward persuasive strategies gave birth to a shift in persuasive technology (PT) design from the one-size-fits-all traditional approach to the individualized approach which conforms to individuals’ preferences. Given that learners’ gender, age, and cognitive level can affect their response to different learning instructions, it is given primacy of place in persuasive educational technology (PET) design. However, the effect of gender, age, and cognitive ability on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Therefore, health interventions that promote the individual components of the SWB will impact positively on people's overall physical health and well-being. There are several social strategies for persuasion (e.g., Reward, Competition, Social Comparison, Social Learning, Trustworthiness and Cooperation) and their effect in behavior change have been identified [9][10][11][12][13][14]. Given its value, PT has seen wide research application in domain such as health [13,14] and education [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, health interventions that promote the individual components of the SWB will impact positively on people's overall physical health and well-being. There are several social strategies for persuasion (e.g., Reward, Competition, Social Comparison, Social Learning, Trustworthiness and Cooperation) and their effect in behavior change have been identified [9][10][11][12][13][14]. Given its value, PT has seen wide research application in domain such as health [13,14] and education [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Oyibo et al [39] found that males are more persuadable by competition and reward than females, especially in collectivist cultures. Similarly, in the education domain, Abdullahi et al [40] found that males are more persuadable by social learning and reward than females, while females are more persuadable by trustworthiness than males. Finally, in path modeling research, Oyibo and Vassileva [41] found that the relationship between reward and competition is stronger for males than females, while the relationship between reward and social learning is stronger for females than males.…”
Section: Gender-based Tailoringmentioning
confidence: 98%
“…Research has however shown that individuals can vary in their sensitivity to different PT strategies. This realization prompted a shift in PT design from the conventional one-sizefits-all approach to a customized approach that adapts to individual preferences (29). In this study, ten susceptibility factors introduced by Modic, Anderson and Palomäki (30) were selected because believe these factors are relevant in scam context and easily acceptable and understood by our respondents, which will promote a consistent interpretation of their responses.…”
Section: Susceptibility To Persuasionmentioning
confidence: 99%